2014
DOI: 10.1103/physrevstab.17.023401
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort electron bunch generation by an energy chirping cell attached rf gun

Abstract: We present a new design for a rf electron gun to be used in ultrashort (∼1 ps) electron bunch generation. Using both simulation and measurement we evaluated the principle of this new type rf gun and were able to confirm an ultrashort bunch generation. During simulation, a bunch length of less than 100 fs(rms) with a 100 pC=bunch charge was confirmed at the optimum operating condition. The principle is to produce a linearly distributed longitudinal phase space by using an attached output cell specially designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…In velocity bunching, it is important how linearly the energy is chirped. In our previous study [16], we confirmed with simulation codes PARMELA [18] and GPT [19] that ECC RF gun can compress a 100 pC bunch into less than 100 fs. However, in our system, the RF power from the klystron is limited to 10 MW so that the maximum electric field on the cathode was expected to be 75 MV/m.…”
Section: Ecc-rf-gunsupporting
confidence: 85%
“…In velocity bunching, it is important how linearly the energy is chirped. In our previous study [16], we confirmed with simulation codes PARMELA [18] and GPT [19] that ECC RF gun can compress a 100 pC bunch into less than 100 fs. However, in our system, the RF power from the klystron is limited to 10 MW so that the maximum electric field on the cathode was expected to be 75 MV/m.…”
Section: Ecc-rf-gunsupporting
confidence: 85%
“…The simulation results are in good accordance with estimations for the length of the compressing region and for the spread in energy encountered in the process of the compression [formulas (23) and (24)]. In the case of 0.3 nC electron bunch, I ¼ 1 kA for l 0 ¼ 0.1 mm and I ¼ 100 A for l 0 ¼ 1 mm.…”
Section: B Axial Compression Of the Electron Bunchsupporting
confidence: 80%
“…However, the negative-mass compression of electron bunches may be of value in itself. In principle, the well-developed methods of сompression of photoinjector bunches based on the energy chirping allow producing bunches with as short lengths as tens fs (∼10 −2 mm) [22][23][24][25]. However, they are successful only when the Coulomb forces inside the bunch are not so important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations